Consciousness and Subjectivity - Miguens, Sofia (Philosophische Analyse / Philosophical Analysis, 2013)
Issues of subjectivity and consciousness are dealt with in very different ways in the analytic tradition and in the idealistic-phenomenological tradition central to continental philosophy. This book brings together analytically inspired philosophers working on the continent with English-speaking philosophers to address specific issues regarding subjectivity and consciousness. The issues range from acquaintance and immediacy in perception and apperception, to the role of agency in bodily 'mine-ness', to self-determination (Selbstbestimmung) through (free) action. Thus involving philosophers of different traditions should yield a deeper vision of consciousness and subjectivity; one relating the mind not only to nature, or to first-person authority in linguistic creatures-questions which, in the analytic tradition, are sometimes treated as exhausting the topic-but also to many other aspects of mind's understanding of itself in ways which disrupt classic inner/outer boundaries.